Potato Peel Starch Bioplastics Reinforced with Microcrystalline Cellulose, PVA, and Chitosan: Mechanical, Thermal, and Antibacterial Properties - Mochamad Viky Afandy; Andoko; Riduwan Prasetya; Muhammad Faizullah Pasha; Mohammad Sukri bin Mustapa (Universitas PGRI Madiun, 2026)
The increasing accumulation of petroleum-based plastic waste has led to the development of biodegradable packaging materials from renewable agro-industrial resources. Therefore, this study aims to synthesize biodegradable potato peel starch/polyvinyl alcohol (PPS/PVA) blend bioplastic films reinforced with microcrystalline cellulose (MCC) and functionalized with chitosan. Films were prepared through solution casting with varied MCC contents and characterized for density, tensile properties, crystallinity, thermal stability, morphology, antibacterial activity, and biodegradability. The results showed that an increase in MCC improved film compactness, tensile strength, crystallinity, and surface uniformity, showing stronger interfacial interactions within the polymer matrix. FTIR confirmed enhanced hydrogen bonding among starch, PVA, chitosan, and MCC, while thermal analysis showed improved resistance to degradation. The produced films also exhibited antibacterial activity against Staphylococcus aureus and Escherichia coli, with the highest performance observed at higher MCC loading. Despite reinforcement, the products remained biodegradable in soil. These results show the potential of PPS/PVA blend bioplastic films containing PPS waste as sustainable materials for active packaging applications.